Listening Otherwise - Cocozza, Sophia. (Tufts University. Tisch Library., 2022)
Thesis (M.A.)--Tufts University, 2022.; Submitted to the Dept. of Music.; Advisor: Melinda Latour.; Committee: Alessandra Campana, and Joseph Auner.; Keyword: Music.